Upaya Penerapan Nilai Karakter Dalam Dunia Pendidikan Menyongsong Era 5.0 - M. Rusdi; Herni Ramayanti; Wia Septia; Abdul Aziz Ridha; Heru Widoyo; Eka Selvi Handayani (Journal on Education, 2023)
The era of globalization demands more and more character building so that graduates from various levels can compete with their peers in other parts of the world. Character is something that is unique only to an individual or group, nation, and is the key to individual success. In accordance with the mission of national education, the purpose of character education is to develop skills and build a valuable national character and civilization in the framework of the formation of the nation's life. In today's world of education, it is very important to apply character values to students to be able to welcome the new Era 5.0. Through this study, it is expected to find the application of character values in the world of education to welcome Era 5.0. This research is a qualitative research with a literature study method. The object of study focuses on analyzing books, scientific articles, and other literacy sources related to efforts to apply character values in education to welcome Era 5.0. Data analysis is carried out by examining the process of strengthening character derived from digital literacy. From the study, efforts to apply character values in education can be carried out in schools and universities so that students have good character values in welcoming the 5.0 era